Evaluation of the environmental hazard of char residues produced in the co-pyrolysis of different wastes :chemical and ecotoxicological characterization - Bernardo, Maria S. (2010)
Char residues produced in co-pyrolysis of different wastes were characterized through chemical and toxicity tests. A fraction of the solid chars was treated by extraction with dichloromethane. Different volatilit fractions present in the extracted and non extrated char were evaluated. A selected group of heavy metals was determined in both chars. Chars were subjected to the leaching test ISO/TS 21268-2 and resulting eluates were further characterized by determining a group of inorganic parameters and concentrations of several organic contaminants. An ecotoxicological characterization was performed by using the bio-indicator Vibrio fischeri. The chemical and ecotoxicological characterization led to a classification on the chars as ecotoxic